Ambiguity of Interpretation: the Gender-Conscious Attitudes in the Dissident Works of the Czech Writer Lenka Procházková - Stohler, Ursula (Poznańskie Studia Slawistyczne, 2016)
This paper explores the presence of gender-conscious attitudes in the works of the Czech author Lenka Procházková (born 1951), a member of the dissident movement during the communist regime. It argues that her writings took issue with patriarchal social structures, yet sometimes camouflaged these challenges behind criticism of the totalitarian rule. These expressions, which one might be tempted to consider as feminist from a Western and 21st-century point of view, emerged within East European dissident culture and probably without exposure to Western feminist concepts. Procházková developed a model of an inner exile for dissidents that originated in a canonical work of Czech literature by Božena Němcová and from which one of her female protagonists draws strength. Thus, her works suggest that Western gender theories are limited in their potential to assess East European dissident women’s writing, when they fail to include local literary traditions.